Gene expressions of SREBP-2, PPARδ, MYH7 and blood lipid changes induced by stretch-shortening cycle exercise - Khalilpour, Armaghan (2011)
The present study was to investigate whether the mRNA levels of the transcription factors, sterol regulatory element-binding protein-2 (SREBP-2), peroxisome proliferator-activated receptor-δ (PPARδ) as well as slow type myosin heavy chain (MYH7) gene are modulated after exhaustive exercise and if so, whether such alterations are related to the percentage of MHC isoforms. In particular, this study was undertaken to examine whether the level of selected blood parameters are influenced by fatiguing stretch-shortening cycle (SSC) exercise. Ten healthy men performed unilateral exhaustive repeated jumps on a special sledge. The maximal voluntary contraction (MVC) was examined before, immediately, 3 and 20 hours after exercise. Selected genes expression in vastus lateralis muscle biopsies were measured by real-time polymerase-chain reaction (RT-PCR) 3 h before, immediately and 3 h after exercise. To test the level creatine kinase (CK) activity, blood lactate (B-La), serum cholesterol (CHOL), high density lipoprotein (HDL) and low-density lipoprotein (LDL), blood sample were collected 3 h before, immediately, 3 and 20 h after exercise. The protein myosin heavy chain (MHC) was determined using electrophoretic separation technique (SDS-PAGE). Declined MVC as well as increased blood lactate and CK activity may imply muscle damage. Significant increase in the level of CHOL, HDL and LDL were observed immediately after exercise that may reflect the synthesis of new cell membranes and healing process of the muscle cells. The expression of PPARδ was decreased significantly after exercise. However, no changes were observed in expressions of SREBP-2 transcripts and MYH7 gene. The expression of PPARδ transcripts was found to be associated with MYH7 mRNA before and after exercise. PPARδ mRNA expression was positively associated with the proportion of the MHCI isoform. Conversely, negative relationship was shown with the proportion of the MHC IIA. These data suggests a single bout of exhaustive exercise provides molecular responses at early stage after exercise. The decreased mRNA concentration of PPARδ may imply that fatiguing exercise bout can initiate a sequence of events towards more glycolytic muscle phenotype. In addition, the association of PPARδ mRNA level with MHCI isoform and MYH7 gene may support the close relationship between indicator of the oxidative fiber types and the regulatory factor of oxidative metabolism. However, the molecular mechanisms underlying these associations are poorly understood. The results concerning the short-term response of PPARδ mRNA after fatiguing exercise that generate challenging questions for further investigation.